The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40256-015-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inpatient Versus Outpatient Initiation on Early Warfarin Dosing

Abstract: Background and Objectives Dosing algorithms for warfarin incorporate clinical and genetic factors but may not account for the numerous comorbidities affecting patients who start warfarin while hospitalized. We aimed to determine whether these algorithms perform differently when warfarin is initiated for inpatients compared with outpatients. Patients and Methods We analyzed a prospective cohort of 1015 participants from the Clarification of Optimal Anticoagulation through Genetics (COAG) trial who were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A study of dosing algorithms comparing inpatients with outpatients showed similarities irrespective of whether dosing was pharmacogenetically or clinically guided (20). Studies confirm the need for more systematic patient instruction at the time of targetspecific administration of oral anticoagulants (TSOACs) and further maintenance therapy (19).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A study of dosing algorithms comparing inpatients with outpatients showed similarities irrespective of whether dosing was pharmacogenetically or clinically guided (20). Studies confirm the need for more systematic patient instruction at the time of targetspecific administration of oral anticoagulants (TSOACs) and further maintenance therapy (19).…”
Section: Resultsmentioning
confidence: 97%
“…The warfarin dosing algorithms were similar for individuals who started warfarin as inpatients and outpatients, irrespective of whether dosing was pharmacogenetically or clinically conducted (20). The risk of hemorrhage is higher in overweight as compared to normal weight patients who are on warfarin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation